Помогите -2х(х²-х+3)+х(2х²+х-5) при х=3; -3

Помогите -2х(х²-х+3)+х(2х²+х-5) при х=3; -3
Гость
Ответ(ы) на вопрос:
Гость
2x^3+2x^2-6x+2x^3+x^2-5x= 3x^2-11x= 3*3^2-11*3=27-33=-5 3*-3^2-11*-3=27+33=60
Гость
-2х(х^2-х+3)+х(2х^2+х-5) 1) х=3 2) х=-3 //Решение: -2х(х^2-х+3)+х(2х^2+х-5) //Для начала упростим: -2х(х^2-х+3)+х(2х^2+х-5) //раскроем скобки -2х^3+2х^2-6х+2х^3-х^2-5х //после получаем х^2-9х //далее решаем 1) х=3 3^2-9*3=9-27=-18 2) х=-3 (-3)^2-9*(-3)=9+27=36 Ответ: 1) -18; 2) 36.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы